Trends of fire deaths and effects of fire safety measures in Taiwan during 1971-2015 - Liao, Yen-Hsiung (International Journal of Health, 2016)
Purpose: Although fire causes 2 % of deaths of the global accidents in Taiwan, injury or death caused by fire is frequent and largely preventable.Approach: Using the Health and Vital Statistics, Fire Losses and Casualties Table, Abridged Life Tables, and Services for Fire Fighting by official publications during 1971-2015, we approached the trends of population, ages, gender, and social costs associated with fatal fire and evaluated the effects of fire safety measures.Results: The higher mortality rate of fire death was in the elders. Fire death rates were 1.92 folds higher risk in males than in females (p < 0.05). The potential years of life lost (PYLL) implied the most efficient evaluation for the fire safety measures. Fire mortality and casualty could be prevented by fire prevention, fire rescue and emergency medical measures effectively. The most significant effect of fire safety measures was evasion training that adopted the indicator of mortality per 102 burned houses (MBH).Conclusions: Therefore, fire prevention efforts should concentrate on males, and elders. The decreasing of fire numbers should be developed and encouraged.